Konsep Dasar Kerjasama Perpustakaan - Yusniah, Yusniah; harahap, Anjelin Rahmi Junaidi; Anggriani, Anggriani; Almira, Chintya (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Domestic library cooperation network is intended as a type of network that occurs in libraries so that cooperative relationships between other libraries are established in an effort to fulfill what is needed by users so that they can satisfy users and the purpose of library services can be achieved. The method used to carry out this research is to conduct a literature study which is further developed in a qualitative descriptive form so that the contents of the journal will provide a more in-depth explanation. The results of the study explain that it is necessary to implement a collaboration network between libraries in either conventional or digital form.. Keywords: network, cooperation, library